2020
DOI: 10.1126/science.aba5899
|View full text |Cite
|
Sign up to set email alerts
|

Seafloor microplastic hotspots controlled by deep-sea circulation

Abstract: Although microplastics are known to pervade the global seafloor, the processes that control their dispersal and concentration in the deep sea remain largely unknown. Here, we show that thermohaline-driven currents, which build extensive seafloor sediment accumulations, can control the distribution of microplastics and create hotspots with the highest concentrations reported for any seafloor setting (190 pieces per 50 grams). Previous studies propose that microplastics are transported to the seafloor by vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
295
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(333 citation statements)
references
References 71 publications
7
295
3
Order By: Relevance
“…While low compared to coastal sediment studies in Australia, the MP counts from our study are high compared to other deepsea sediment analyses globally (Table 4). Four other studies of MPs in deep-sea sediment reported MP counts similar to ours including samples from the Arctic (Bergmann et al, 2017), the Mediterranean (Woodall et al, 2014;Kane et al, 2020), the North Atlantic (Woodall et al, 2014), and the Western Pacific (Zhang et al, 2020;Table 4). Even in these instances, however, the MP counts we observed were more than double those reported in other studies, in spite of our careful measures to exclude contamination and not including fibers.…”
Section: Microplastic Fragments In Deep-sea Sedimentssupporting
confidence: 82%
See 1 more Smart Citation
“…While low compared to coastal sediment studies in Australia, the MP counts from our study are high compared to other deepsea sediment analyses globally (Table 4). Four other studies of MPs in deep-sea sediment reported MP counts similar to ours including samples from the Arctic (Bergmann et al, 2017), the Mediterranean (Woodall et al, 2014;Kane et al, 2020), the North Atlantic (Woodall et al, 2014), and the Western Pacific (Zhang et al, 2020;Table 4). Even in these instances, however, the MP counts we observed were more than double those reported in other studies, in spite of our careful measures to exclude contamination and not including fibers.…”
Section: Microplastic Fragments In Deep-sea Sedimentssupporting
confidence: 82%
“…The high variance at a core level points to the high heterogeneity of MP deposition on the seabed and the likely influence of oceanographic conditions at a very fine scale. The small size and variable density of MPs suggest these small particles are easily transported via ocean currents (Lusher, 2015;Kane et al, 2020), climate and weather changes (Welden and Lusher, 2017), fish and animal behavior (Davidson, 2012;Cózar et al, 2014), biofouling (Ye and Andrady, 1991;Fazey and Ryan, 2016), and buoyant rise velocity (Reisser et al, 2013).…”
Section: Variability In Microplasticsmentioning
confidence: 99%
“…This might be the reason why submarine canyons have been reported to be hotspots for MaP and microplastic [105]. Additionally, near-bed thermohaline-driven currents influence the accumulation of plastic items on the seafloor [106].…”
Section: Transport In Aquatic Environmentsmentioning
confidence: 99%
“…In addition, it is acknowledged that to track the distribution of microplastics is difficult due to the disagreement between buoyancy capacity and the sinking nature of most particles (Hardesty et al, 2017;Cózar et al, 2017). Therefore, to couple predictions from different water masses and sediments along the entire ocean basin will be the only way to understand how floating MPs sink towards sediments and then come back to surface following major oceanic dynamics (Mountford and Morales Maqueda, 2019;Kane et al, 2020).…”
Section: Introductionmentioning
confidence: 99%